The Relationship of Sex, Maternal Education and Exclusive Breast Milk Consumption with Stunting Events in Toddlers - Rusmiyati Rusmiyati; Roselina Panghiyangani; Syamsul Arifin; Meitria Syahadatina Noor; Husaini Husaini (Jurnal Berkala Kesehatan, 2023)
Stunting is a condition of child's height growth is impaired. One in four toddlers experience stunting, characterized by stunted growth. Prevalence of stunting in toddlers nationally remains high at 36.8%. It has not reached WHO target, which is below 20%. Government has determined stunting as one of the priority programs, namely the Healthy Indonesia Program with Family Approach to reduce the incidence of stunting in toddlers. Therefore, a meta-analysis study analyzes the relationship between sex, mother's education and exclusive breastfeeding consumption with the incidence of stunting in toddlers by applying PRISMA protocol. The results was no relationship between sex and the incidence of stunting in toddlers with OR value of 1.087 (95% CI 0.960 - 1.231), there was a relationship between mother's education and the incidence of stunting in toddlers with OR value of 1.850 (95% CI 1.550 - 2.208), and there is a relationship between exclusive breastfeeding and the incidence of stunting in toodlers with OR value of 1.657 (95% CI 1.004 2.737) and shows no publication bias with funnel plot symmetry. So it can be concluded that there is no relationship between sex and the incidence of stunting, and there is a relationship between maternal education and exclusive breastfeeding consumption with stunting in toddlers.